Killing commendatore : a novel - Murakami, Haruki, 1949- (Knopf, 2018)
"The much-anticipated new novel from the internationally acclaimed, best-selling author of 1Q84 and Colorless Tsukuru Tazaki and His Years of Pilgrimage, Killing Commendatore is an epic tour de force of love and loneliness, war and art--as well as a loving homage to The Great Gatsby--and a stunning work of imagination from one of our greatest writers"--